## gerryliyana 2 years ago I need help ! Pleaseee Solve (x-2y +1) dx + (4x -3y -6) dy = 0

1. xon1300

use green's theorem ( http://en.wikipedia.org/wiki/Green%27s_theorem )

2. gerryliyana

Seriously??? can you tell me how to solve it?

3. xon1300

It's been a while since i took calculus 3

4. gerryliyana

then???

5. gerryliyana

have you any idea, @Cynosure-EPR ?????

6. Cynosure-EPR

I'm sorry =( I do know how to do it but I'm rushed with a programming assignment (worth 40% of grade) due at midnight =(

7. gerryliyana

ok no problem @Cynosure-EPR :) good luck for u :)

8. gerryliyana

@zepp have u any idea??

9. zepp

Nope, I'm only at Calc II, sorry ):

10. gerryliyana

ok np @zepp thank u for coming :)

11. mahmit2012

|dw:1354582292989:dw|

12. ChmE

$(x-2y +1) dx + (4x -3y -6) dy = 0$$-(x-2y +1) dx = (4x -3y -6) dy$$\frac{ dy }{ dx }=\frac{ -(x-2y+1) }{ (4x -3y -6) }$

13. ChmE

Do you know how to do separation of variables? http://en.wikipedia.org/wiki/Separation_of_variables

14. ChmE

This looks like a diff eq question

15. ChmE

nvm, I don't think we can use that here

16. gerryliyana

then ???? how to solve y?? i really know separation variable, but in this case that method cannot work,

17. gerryliyana

yes.., i think so.., we cannot use that in this case.., :)

18. ChmE
19. ChmE

My teacher skipped partial derivatives and that looks like what is needed for this problem. I'm going to tapout. Good luck

20. gerryliyana

i see.., wonderful site for me.., thank u @ChmE,

21. sirm3d

solve the system of equation $\large \left(\begin{matrix}x-2y+1=0 \\ 4x-3y-6=0\end{matrix}\right)$

22. sirm3d

when you get the solution, say x0 and y0, use u = x - x0 and v = y - y0. try this @gerryliyana

23. gerryliyana

ok.., i'll try

24. sirm3d

did you get this DE? $\large (u-2v)du + (4u-3v)dv=0$ x changed to u, y changed to v, the constants +1 and -6 disappeared.

25. gerryliyana

$\left( \frac{ x - 2y + 1 }{ 4x -3y - 6 } \right) \times \left[ \frac{ 4 }{ 1 } \right]$ $\left( \frac{ 4x - 8y + 4 }{ 4x - 3y -6 } \right) = 0$ $\left( \frac{ 4x - 8y = -4 }{ 4x -3y= 6 } \right)$ -------------------------------------------- __ $-8y -(-3y) = -10 \rightarrow y = 2$ $4x - 3(2) = 6 \rightarrow x = 3$

26. sirm3d

on the right track. now, u = x - 3 and v = y - 2

27. gerryliyana

OMG..., my connection is lost, and I lost all my type, :(

28. sirm3d

hahaha. enter them a few equations at a time.

29. sirm3d

don't worry. you are not the first one.